INFLUENCE OF SERVICE QUALITY AND EMPLOYEE PERFORMANCE TOWARDS CUSTOMER SATISFACTION IN USING LOAN SERVICES AT THE MANADO PAWNSHOP OFFICE - Venna Aprilian Dalentang; Is Fadhilah (Suluh Adiluhung Publisher (SAPub), 2024)
This research aims to analyze the influence of service quality and employee performance towards customers' decisions in using lending services at the Manado Pawnshop Office. This research is important considering the strategic role of Pawnshop as a financial institution that provides collateral-based lending services. Data was collected through a survey of 150 customers who used lending services at the Manado Pawnshop Office. The analytical method used is multiple linear regression analysis to measure the influence of service quality and employee performance on customer decisions. The research results show that service quality has a significant positive influence on customer decisions. This indicates that aspects such as reliability, responsiveness and good service guarantees increase customer satisfaction and encourage them to use lending services. Apart from that, employee performance has also been proven to have a significant positive influence on customer decisions. The performance of employees who are professional, responsive and knowledgeable about Pawnshop products is a determining factor in customer decision making. The conclusion of this research is that both service quality and employee performance are key factors that influence customers' decisions in using lending services at the Manado Pawnshop Office. The practical implication of these findings is that Pawnshop needs to continue to improve service quality and employee performance to maintain and increase customer trust. It is hoped that this research can contribute to literature related to service management and human resource development in the financial sector.